Juridical Text in the Aspect of Translation (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The paper studies specific, relevant in  the process of translation features of juridical texts, the elements of the text bearing cognitive information, the peculiarities of translating English juridical terminology into Ukrainian. It deals with the major translation techniques in this lexical subsystem. In juridical translation the main goal is to identify the situation described in the original. The systemic relevant features of the juridical text in translating process are: the use of juridical terminology which is rendered by means of monosemantic equivalents; the use of passive constructions rendered by grammatical equivalent correspondences or by appropriate transformations; generalizing semantics of the subject rendered by variant correspondences; the neutral background of the bookish literary norm with its lexical and syntactic peculiarities; the variability of syntactic structures and types of logical cohesion. Juridical terminology as the major  cognitive component of the juridical text is subject to various operations in the process of translation. The first group of operations is presented by translational transcription and loan translation. The second group of operations includes all types of lexical transformations – generalization, concretization, sense development. The third group of translating procedures comprises all types of grammatical transformations, or grammatical replacements. The forth group includes changes of both lexical and grammatical nature – antonymic translation, addition, omission, explication.
Keywords: legal document; cognitive information; juridical terminology; translation transformation